Addressing the Gender Gap in Innovative Companies: Does the Culture of Innovation Turn Women Away? - Day, Geneva (Edelweiss Applied Science and Technology, 2018)
There is a large gender gap in technological roles at highly innovative companies in the United States that reduces their ability to exploit a diverse knowledge base. Diversity in human capital is key to the success of innovations in an organization, this paper proposed that it is the inherent characteristics of the culture of innovation that prevents women from applying and staying in innovative roles. Using thematic review, this paper analyzed research in the areas of the culture of innovation as well as the organizational cultural preferences of women to understand what values are incongruent that could be causing this gap. Results showed that there were many incongruent factors between the culture of innovation and preferences in organizational culture for women and that this is a valid reason why these roles are not sought out of kept by women. The results suggested that managers should implement and sustain supportive values to balance an organizational culture that needs to focus on innovation, but also wants to have diversity of thought.